Historikal – Praksis Pendidikan Agama Kristen dan Filsafat Yunani Klasik - Alfonso Munte (Sekolah Tinggi Agama Kristen Samarinda, 2023)
Abstract: Background of this research namely the researcher is in the space not specifically looking at the historicity of Christian Religious Education as an era, but rather historical reflections in the vitalization of Christian education which is not only in the school bench space, but also in the church and the outdoors. Research methods are based on qualitative research with data search techniques through literature studies, namely through books and the availability of national or international journals. Results showed that the commodities of knowledge in Classical Greek, medieval, modern and post-structuralist times, Christian education is in its unique form while dwelling on the same form and purpose, namely education in schools, churches and also outside schools. Christian education itself cannot exist without the presence of formal and/or informal education throughout the ages. Abstrak: Latarbelakang penelitian ini yakni peneliti berada pada ruang tidak spesifik melihat historisitas Pendidikan Agama Kristen sebagai sebuah pengotakan zaman, namun lebih kepada refleksi sejarah dalam penghidupan pendidikan Kristen yang tidak saja berada pada ruang bangku sekolah, tapi juga berada di gereja dan alam bebas. Metode penelitian peneliti berada pada penelitian kualitatif dengan teknik pencarian data melalui studi kepustakaan yakni melalui buku-buku dan ketersediaan jurnal-jurnal nasional ataupun internasional. Hasil penelitian menunjukkan bahwa komoditas pengetahuan pada zaman Yunani Klasik, pertengahan, modern dan postrukturalis, pendidikan Kristen merupa dalam bentuk unik sekaligus berdiam pada wujud dan tujuan yang sama yakni pendidikan di sekolah, gereja dan juga di luar sekolah. Pendidikan Agama Kristen itu sendiri tidak dapat hadir tanpa kehadiran pendidikan formal dan/atau informal sepanjang jaman.